Design and development of sri single seedling transplanting implement with seedlings in semi-dried clay media - Zubairu, Usman Bashar (2016)
In rice production, seedling quality and transplanting potentials stand as a prerequisite for the proper completion of rice production operations in securing optimum yield. The overall objective of this research was to develop a transplanting implement capable of placing rice seedling singly into the field by dropping through a gated opener with respect to SRI planting and spacing conditions deprived from the existing methods of picking fingers by the conventional transplanting machines. It has been built with the aim of using seedlings established from SRI-tray of 924 separated growing cavities. It was designed with adjustable spacing options on both within and between rows of 25 cm, 30 cm and 40 cm respectively in order to suite intending SRI practitioners preference. Accordingly, it has been set to provide nine SRI spacing options (25 cm × 25 cm, 25 cm × 30 cm, 25 cm × 40 cm, 30cm × 30 cm, 30 cm × 40 cm and 40 cm × 40 cm, respectively). The performance of SRI single seedling transplanting implement was evaluated and the measured parameters were suitable growing media, planting speed, percentages of single seedling placement per hill, missing hills and multiple planting. Others include turning head, loading time, angle of repose, field capacity and field efficiency. The planting data indicated that speed of operation run at 0.18 m/s reported high significance percentage of single seedling per hill when subjected to spacing patterns of 25 × 35 cm (84%), 25 × 25 cm (81%), 30 × 30 cm (73%) and 40 × 40 cm (83%) but decreased with the increasing speed of 0.45 m/s as 53%, 56% and 72%; thus surprising stability on 40 × 40 cm of 83%. The results obtained on growing media revealed that clay with compost had the highest significance with respect to the weight of seedling (25.3 g) giving the loosening index of 66 seconds and the planting depth of 16 mm when transplanting in the field. The results obtained from field capacity and field efficiency revealed that when the tractor was maintained to 0.18 m/s, the field capacity and field efficiency reported the values of 1.29 ha/hr and 79.5%, respectively but when the speed was fixed or increased to 0.45 m/s these values changed to 1.55 ha/hr and 75%.